Identification and molecular characterization of a phytoplasma associated with sunflower in Argentina - Guzmán, Fabiana; Giolitti, Fabian; Fernandez, Franco Daniel; Nome Docampo, Claudia; Lenardon, Sergio Luis; Conci, Luis Rogelio (Springer, 2018)
Sunflower (Helianthus annuus L.) plants showing capitulum with virescence, phyllody and flower malformation, shortened internodes and abnormal branches were found in a field in Pedro Luro (Buenos Aires province, Argentina). Pleomorphic bodies resembling phytoplasmas were observed in sieve tube elements of symptomatic plants but not in healthy ones. DNA from all symptomatic sunflower plants analysed yielded, in direct PCR with phytoplasma universal primers P1/P7 and R16F2n/R2, fragments of expected size 1.8 kb and 1.2 kb, respectively. The phytoplasma associated with the disease, was named Sunflower Phyllody (SunPhy). Real and putative RFLP of the 16S rDNA showed the affiliation of SunPhy to 16SrIII (X-disease group), subgroup J. The 16S rDNA sequence from SunPhy showed the highest identity (99 %) with 16SrIII members and the phylogenetic tree confirmed a closer relationship to subgroup J of the 16SIII ribosomal group. This is the first report of a phytoplasma related to the 16SrIII group affecting sunflower.